Histological changes following Nd YAG laser photocoagulation of canine gastric mucosa. Issue 10 (October 1983) - Kelly, D F; Bown, S G; Calder, B M; Pearson, H; Weaver, B M; Swain, C P; Salmon, P R
Abstract : Tissue changes produced in the dog stomach by exposure to a Nd YAG laser varied from mild mucosal oedema to cell vaporisation. Intermediate degrees of damage caused a marked inflammatory response leading to extensive fibrosis in the submucosa and muscularis propria. The true extent of tissue damage was not apparent immediately, and treated mucosa that initially appeared intact sometimes sloughed several days later to leave an ulcer. The extent of damage and the rate of healing depended on the amount of laser energy used. With pulses at optimum laser power (75 w) and exposure time (0.4 sec), however, haemostasis was achieved in induced ulcers with total energy concentrations that did not produce full thickness tissue damage nor alter the healing rate from that observed in untreated ulcers. Thermal contraction was the primary haemostatic mechanism, thrombosis only occurring as a secondary effect.